Cognitive load of three levels of object categories in reading tasks: evidence from eye movements. - Li, Jing; Luo, Chuanwei; Xiao, Jiao; Wang, Yimeng (Language, Cognition & Neuroscience, 2025)
To evaluate the cognitive load of Chinese basic-level categories, eye movement measures of naturalistic reading and proofreading tasks were used. 36 participants completed two reading tasks, each involving 21 groups of sentences containing category terms of varying levels. The results indicate that the difficulty of reading tasks does not influence initial category processing, but only affects late overall processing. The cognitive economy of basic-level categories appears as the difficulty and complexity of reading tasks increase. Specifically, in the proofreading task, the cognitive load of basic-level categories is lower than that of the subordinate categories. The processing difficulty of basic-level categories in naturalistic reading is equivalent to that of the superordinate category in the overall processing. Furthermore, generalisation plays the same role as gestalt in the judgment of category cognitive economy. It results in smaller differences in processing difficulty and cognitive load between the superordinate and basic-level categories in local processing.